Reduction and analysis of SANS and USANS data using IGOR Pro - Kline, Steven R. (Journal of applied crystallography, 2006)
A software package is presented for performing reduction and analysis of small‐angle neutron scattering (SANS) and ultra‐small‐angle neutron scattering (USANS) data. A graphical interface has been developed to visualize and quickly reduce raw SANS and USANS data into one‐ or two‐dimensional formats for interpretation. The resulting reduced data can then be analyzed using model‐independent methods or non‐linear fitting to one of a large and growing catalog of included structural models. The different instrumental smearing effects for slit‐smeared USANS and pinhole‐smeared SANS data are handled automatically during analysis. In addition, any number of SANS and USANS data sets can be analyzed simultaneously. The reduction operations and analysis models are written in a modular format for extensibility, allowing users to contribute code and models for distribution to all users. The software package is based on Igor Pro, providing freely distributable and modifiable code that runs on Macintosh and Windows operating systems.